Labor Supply Response to Welfare Programs: A Dynamic Analysis - Blau, David M.; Robins, Philip K. (Journal of Labor Economics, 1986)
Previous static analyses of the work disincentive effects of welfare programs are extended to a dynamic context. Using a sample of continuous longitudinal labor market histories, estimates are derived for welfare-nonwelfare differences in labor market flows among the states of employment, unemployment, and nonparticipation. The estimates are used to identify the main sources of the lower employment and labor force participation rates and higher unemployment rate of welfare recipients. The findings indicate that welfare programs have substantial effects on virtually every labor market transition examined but that the primary source of the static work disincentive effect is slower entry into employment.